Older Adults' Recognition of Tradeoffs in Healthcare Decision Making - Case, Siobhan M. (J Am Geriatr Soc, 2015)
OBJECTIVES: To examine older persons’ understanding of healthcare decision making involving tradeoffs. DESIGN: Cross-sectional survey SETTING: Primary care clinics PARTICIPANTS: Community-living persons age 65 years and older MEASUREMENTS: After being primed to think about tradeoffs with a focus on chronic disease management, participants were asked to describe a decision they had made in the past involving a tradeoff. If they could not, they were asked to describe a decision they might face in the future and were then given an example of a decision. They were also asked about communication with their primary care provider about their priorities when faced with a tradeoff. RESULTS: Of the 50 participants, 44 (88%) were able to describe a healthcare decision involving a tradeoff; 25 provided a decision in the past, 17 provided a decision they might face in the future, and 2 provided a future decision after hearing an example. One participant described a non-medical decision and two participants described goals without providing a tradeoff. Of the healthcare decisions, 26 involved surgery, seven were end-of life decisions, seven regarded treatment of chronic disease, and four involved chemotherapy. When asked whether their providers should know their health outcome priorities, 44 (88%) replied yes; 35 (70%) believed their providers knew their priorities; however, only 18 (36%) said that they had a specific conversation about priorities. CONCLUSION: The majority of participants were able to recognize the tradeoffs involved in healthcare decision making and wanted their providers to know their priorities regarding the tradeoffs. Despite being primed to think about the tradeoffs involved in day-to-day treatment of chronic disease, participants most frequently described episodic, high-stakes decisions including surgery and end-of-life care.